The Effect of Nahwu-Shorof Learning and Students' Reading Ability on the Learning Outcomes of the Yellow Book at the Al-Qismul 'Ali Al-Washliyah Madrasah Kedaisianam Batubara - Nurmawati Nurmawati; Salminawati Salminawati; Aimanun Aimanun (Budapest International Research and Critics University, 2022)
This study aims to determine: (1) the learning outcomes of the Al-Qismul 'Ali Al-Washliyah Kedaisianam Batubara Madrasah students who are taught by the induction method and the analogy method, (2) the learning outcomes of the Al-Qismul 'Ali Al-Madrasah students' yellow book learning outcomes. Washliyah Kedaisianam Batubara with high and low reading abilities, and (3) the interaction between nahwu shorof learning and students' ability to read on the learning outcomes of the yellow book students of Madrasah Al-Qismul 'Ali Al-Washliyah Kedaisianam Batubara. The research was conducted at Madrasah Al-Qismul 'Ali Al-Washliyah Kedaisianam Batubara. This type of research is a quasi-experimental quantitative research model. Based on the Cluster Random Sampling technique, one class is taught by the induction method and one class is taught by the analogy method. The research instrument is a test used to obtain data on student learning outcomes. The normality test for learning outcomes data is the Liliefors test and the homogeneity test is the Fisher's test and Bartlett's test. The analysis technique is a two-way ANOVA at a significance of = 0.05, followed by the Scheffe test. The research findings show: (1) the learning outcomes of the yellow book students who were taught by the induction method at the students of Madrasah Al-Qismul 'Ali Al-Washliyah Kedaisianam Batubara were higher in the yellow book learning outcomes of students who were taught using the analogy method. This is proven by testing the research hypothesis with statistical results Fcount = 11.78 while the value of Ftable = 4.018 for dk (1.55) and the real level = 0.05, (2) learning outcomes of students with high reading ability are higher from the results of learning the yellow book of students with low reading skills. This is proven by testing the research hypothesis with statistical results Fcount = 26.82 while the value of Ftable = 4.018 for dk (1.55) and the significance level = 0.05, and (3) there is an interaction between nahwu-shorof learning and reading ability on the yellow book learning outcomes at Madrasah Al-Qismul 'Ali Al-Washliyah Kedaisianam Batubara. This is proven by testing the research hypothesis with statistical results Fcount = 17.29 while the value of Ftable = 4.018 for dk (1.55) and the significance level = 0.05.